Metrics to Millions: Understanding the Drivers of NBA Player Salaries - Zou, LinJun (Technium Business and Management, 2025)
This research analyzes how NBA player performance metrics: age, points, assists, and rebounds per 36 minutes affect player salaries. The results indicate that scoring (points per 36 minutes) is the strongest determinant of salary, and the playmaking ability is less strong than scoring but also significantly affect the salary (assists per 36 minutes). While age has a moderate yet noteworthy influence, rebounding (rebounds per 36 minutes) has minimal impact. These findings indicate that modern NBA salary structures highlight skills, particularly scoring and playmaking, over the traditional contributions during the game like rebounding. The study offers valuable industry insights for players, agents, and team managers, aims to guiding better understand the metrics that most influence salary negotiations and the industry dynamics.